Fault-Tolerant Method for Detecting Coverage Holes of Wireless Sensor Networks - Xiang-yi Chen; Fei Li; Liang-min Wang (Institute of Advanced Engineering and Science, 2012)
Coverage is one of the fundamental problems in Wireless Sensor Networks (WSNs) since it is an important measure of Quality of Service (QoS) for the network’s applications. However, due to random development, power exhausting, intrusion and attacking of other malice nodes, coverage holes often appear and undermine the networks. In order to solve this problem, we present a decentralized, coordinate-free, and fault-tolerant algorithm for detecting coverage holes, which can be run on a single node. It only needs the connectivity information gathered from one-hop neighbors of the running node. During the detection process, maximal simplicial complex of the local area is required to determine whether the node is at the boundary of a hole or not. After the information of sensors around the coverage hole will be processed by the base station, and the size of coverage holes will be obtained. Simulation results show the fault tolerance of the proposed method. Meanwhile the detection accuracy, error-detection and missed-detection are compared with some related methods reported recently. The results also show that our method is effective, robust, and especially suitable for large scale networks. DOI: http://dx.doi.org/10.11591/telkomnika.v10i4.873